Recent Progress in Luminescent Cu(I) Halide Complexes: A Mini-Review - Mensah, Abraham; Shao, Juan-Juan; Ni, Jian-Ling; Li, Guang-Jun; Wang, Fang-Ming; Chen, Li-Zhuang (Frontiers in Chemistry, 2022)
Copper(I) halide complexes are well sought-after materials due to their rich structural diversities and photophysical properties. Profoundly, there is a direct relationship between each structural variation and luminescence of these complexes, for a purported use. In this review, recent publications within the last 2 years about copper(I) halide complexes, centering on their structural dimensionalities with derivatives of nitrogen, phosphorus, and sulfur ligands, have been considered alongside their effects on luminescence.